Restraining population growth in three chinese villages, 1988-93 - Greenhalgh, S.; Chuzhu, Zhu; Nan, LI
tbls., gráfs.
pp. 365-395
Keywords: China; Crecimiento Demografico; Fecundidad; Planificacion Familiar